DEVELOPMENT OF EDUCATIONAL VIDEO ANIMATION OF WATER CYCLE MATERIALS IN CLASS 5 ELEMENTARY SCHOOL (SD) STUDENTS - Marliza (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Video learning media can assist teachers in conveying learning and facilitatingstudent learning with a fun and non-monotonous learning atmosphere so that itcan improve student achievement in learning and students' thinking skills. Thepurpose of developing this media is to produce valid and appropriate animatedcartoon educational video products for fifth grade elementary school students.This research method uses the ADDIE model and has been modified by theresearcher. The purpose of this research is to develop interactive multimedia onthe topic of the water cycle for fifth grade elementary school students. This typeof research is development using the ADDIE development model. There were12 research subjects consisting of 2 material experts and 2 learning mediaexperts and 2 science teachers. The test subjects were fifth grade students atBakongan 3 Public Elementary School. Collecting methods namelyobservation, interviews, and questionnaires. . Based on the results of the trialsconducted, it was concluded that the animated cartoon educational videos thathad been developed belonged to the valid category. Therefore, this animatedcartoon educational video media is valid and can be applied in learningactivities. The development of this animated cartoon educational video isexpected to be developed by developers who have ideas about the same mediaas well as being a reference.